Analisis Kesesuaian Tingkat Kebisingan Salah Satu Bandara di Jawa Timur terhadap Baku Mutu Lingkungan Menggunakan Pemodelan Spasial di Permukiman Sekitar - Sandi Alifian Finardi; Restu Hikmah Ayu Murti (Jurnal Serambi Engineering, 2025)
The increase in operational activities at one of the airports in East Java has led to elevated noise levels in the surrounding areas, particularly in residential zones. This study aims to analyze the conformity of noise levels with environmental quality standards using a spatial modeling approach. The method applied is descriptive quantitative, employing spatial analysis based on secondary data obtained from the Environmental Management and Monitoring Plan (RKL-RPL) documents. Noise data were examined from five monitoring points and visualized through maps using GIS software. The results indicate that most observation points recorded noise levels exceeding the threshold limits stipulated by Ministry of Environment Decree No. 48 of 1996 and were also found to be inconsistent when compared to area classifications based on the WECPNL method. The implications of these findings highlight the necessity for evaluating the effectiveness of RKL-RPL implementation, strengthening supervisory roles, and formulating mitigation strategies, such as the development of green open spaces and the adoption of environmentally friendly flight paths, to minimize noise impacts on surrounding communities.